The Role of Parents in Instilling a Love for the Environment in Children - Siregar, Khalida Ziah Sukmana; Sitorus , Mayang Sari; Tarigan, Salsah Nabila; Sit, Masganti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to describe the role of parents in instilling a love for the environment in early childhood. The method used in this study is descriptive with a qualitative design. The subjects of this study are parents and early childhood children at school. The instruments used to collect data in this study are participant observation, interviews, and documentation. The results of the study indicate: 1. The role of parents as educators in instilling environmental love in children. Parents always teach their children to love the environment by not littering, gardening, caring for plants, washing hands with soap before and after meals, and bathing with soap; 2. The role of parents as guides in instilling a love for the environment in children. Parents always supervise and guide their children's activities both inside and outside the home so that children become accustomed to loving the environment. Thus, the roles applied by parents in instilling environmental love in early childhood are evident.